Global Trends and Recommended Configurations in Personal Breathing-Zone Nanoparticle Sampling Methods for Workers: An Updated Systematic Review (2000–2025) - Silaban, Anita; Banjarnahor, Riri (Civiliza Publishing, 2025)
This PRISMA-based systematic review synthesized 12 studies (2000–2025) on personal breathing-zone (PBZ) nanoparticle sampling among workers. The analysis categorized direct-reading devices (CPC, DiSCmini, SMPS, ELPI) and filter-based samplers (NRD, PENS, TDS) by metric, size range, and portability. Global trends indicate a post-2015 shift toward portable, multimodal instruments, though evidence gaps remain, especially in low- and middle-income countries. The combined use of the NRD (for deposition-relevant, composition-specific analysis) and CPC/DiSCmini (for real-time exposure patterns) is identified as the most comprehensive configuration. Standardized reporting of flow, background, and uncertainty, is recommended to enhance comparability and occupational health decision-making.